2011
DOI: 10.1080/ac.66.6.2136966
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic left ventricular lead implantation

Abstract: Minimally invasive left ventricular lead implantation is a safe procedure with excellent acute threshold capture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Previous studies have been published on the VAT technique . We showed that the VAT approach is safe and effective.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Previous studies have been published on the VAT technique . We showed that the VAT approach is safe and effective.…”
Section: Discussionmentioning
confidence: 58%
“…19 Previous studies have been published on the VAT technique. [19][20][21]24,[28][29][30][31][32][33][34][35][36] We showed that the VAT approach is safe and effective. We included both patients who had undergone unsuccessful de novo transvenous LV lead implantation and patients who had…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…17 In Table 1 we report the published studies about the VAT technique in CRT procedures. 11,15,[18][19][20][21][22][23][24][25][26][27][28] Most of the published studies are retrospective or observational studies, not randomized and in only two paper a comparison with a transvenous control group is reported. 28,29 Marini et al 29 show that, in patients in whom transvenous implantation of the LV lead has previously failed, epicardial implantation through the VAT approach is safe and effective.…”
Section: Video-assisted Thoracoscopic Lead Implantation Technique Dur...mentioning
confidence: 99%